LEGITIMACY OF A FIXED-TERM EMPLOYMENT CONTRACT BASED ON REMOTE WORK CONCEPT FROM THE PERSPECTIVE OF THE JOB CREATION ACT - Putu Bella Mania Madia; I Nyoman Bagiastra; I Wayan Novy Purwanto (POLICY, LAW, NOTARY AND REGULATORY ISSUES, 2022)
Labor issues are a social, political and economic phenomenon in modern countries, including Indonesia, and require a way that is no longer conventional in improving the system in employment. As such, remote working can be the solution. The implementation of Remote Working in Indonesia depends on three legal aspects, namely the Criminal Code, the Job Creation Act along with the Labor Law, and the ITE Law. This study aims to analyze the Fixed-Term Employment Contract (PKWT) work relationship based on remote work concept from the perspective of the job creation act and find out the implementation and problems of Fixed-Term Employment Contract. This study employs a normative legal research technique derived from laws and regulations employing a library research technique. According to the findings of this study, Fixed-Term Employment Contract with the Remote Working concept must also adhere to the Labor Law and the Job Creation Act. Besides, the parties who engages on the Fixed-Term Employment Contract must also consider a number of additional legal factors in order to ensure the agreement's legitimacy and the protection of each party's rights and obligations. Despite the passage of the Job Creation Act, it turns out that there are still several issues that require attention.